PENERAPAN PEMBERIAN PAKAN BERBAHAN ELA SAGU PADA PETERNAKAN AYAM KAMPUNG DI DUSUN WARINGIN CAP DESA WAYAME - Radjab Radjab; Tabita Ralahalu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2021)
The community service activity aims to solve the problems experienced by the farmer group located in the Waringin Cap, Wayame village. The solutions offered by several approaches methods, which is: (1). social approach with the village government and the farmer group, (2). The counseling implementation, lecture and debriefing session about various practical knowledge related to the feeding process, the distribution of brochures about nutrient levels of feed ingredients in Ambon and the need of chicken's feed in each phase of life as a references which can be used at any time when needed by society. In addition, demonstration plot of the chicken rations preparation and also demonstration plot in providing rations are practiced according to the needs of the production type. The growth of native chickens from these demonstration plot resulted in better growth. This was recognized by the farmer that the chickens fed by the demonstration plot method had more significant increase in growth compared to the chickens fed by the farmer. The conclusion of this community service activity is the farmers have skills in utilizing the ela Sago (sago waste) as agricultural waste to feed native chickens